Cost-effectiveness of the sequential application of tyrosine kinase inhibitors for the treatment of chronic myeloid leukemia. Issue 8 (3rd August 2015) - Rochau, Ursula; Sroczynski, Gaby; Wolf, Dominik; Schmidt, Stefan; Jahn, Beate; Kluibenschaedl, Martina; Conrads-Frank, Annette; Stenehjem, David; Brixner, Diana; Radich, Jerald; Gastl, Günther; Siebert, Uwe
Abstract : Several tyrosine kinase inhibitors (TKIs) are approved for chronic myeloid leukemia (CML) therapy. We evaluated the long-term cost-effectiveness of seven sequential therapy regimens for CML in Austria. A cost-effectiveness analysis was performed using a state-transition Markov model. As model parameters, we used published trial data, clinical, epidemiological and economic data from the Austrian CML registry and national databases. We performed a cohort simulation over a life-long time-horizon from a societal perspective. Nilotinib without second-line TKI yielded an incremental cost-utility ratio of 121 400 €/quality-adjusted life year (QALY) compared to imatinib without second-line TKI after imatinib failure. Imatinib followed by nilotinib after failure resulted in 131 100 €/QALY compared to nilotinib without second-line TKI. Nilotinib followed by dasatinib yielded 152 400 €/QALY compared to imatinib followed by nilotinib after failure. Remaining strategies were dominated. The sequential application of TKIs is standard-of-care, and thus, our analysis points toward imatinib followed by nilotinib as the most cost-effective strategy.